2013
DOI: 10.1002/em.21805
|View full text |Cite
|
Sign up to set email alerts
|

Omics in population studies: A molecular epidemiology perspective

Abstract: The convergence of striking developments in (bio)-technology, increasing availability of biobanked samples, and advances in biostatistics and bio-informatics allow an optimistic outlook for epidemiological research. In this special issue on Omics in Population Studies: A Molecular Epidemiology Perspective we explore and reflect on the potential of these new developments in both exposure science and clinical research since they provide the essential link between exposure and disease and may enable scientists to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It has been suggested that an optimistic outlook for epidemiology is being offered by the “convergence of striking developments in biotechnology, the increasing availability of biobanked samples, and advances in biostatistics and bioinformatics.” 71 We need to move these rapidly evolving investigations out of case-control studies within specialty clinics and into the larger community where AD cases can potentially be identified at all disease stages including preclinical disease, and with all the common comorbidities with which therapeutics must contend. Omics provides an opportunity for precision medicine, 72 in that it can identify subgroups with different pathways defined, for example, by different polygenic scores.…”
Section: Molecular Epidemiology and Omicsmentioning
confidence: 99%
“…It has been suggested that an optimistic outlook for epidemiology is being offered by the “convergence of striking developments in biotechnology, the increasing availability of biobanked samples, and advances in biostatistics and bioinformatics.” 71 We need to move these rapidly evolving investigations out of case-control studies within specialty clinics and into the larger community where AD cases can potentially be identified at all disease stages including preclinical disease, and with all the common comorbidities with which therapeutics must contend. Omics provides an opportunity for precision medicine, 72 in that it can identify subgroups with different pathways defined, for example, by different polygenic scores.…”
Section: Molecular Epidemiology and Omicsmentioning
confidence: 99%
“…The biological processes described in the developmental programming hypothesis are themselves determined by social and environmental exposures . Epigenetics and humanomics elucidate the importance of these exposures to the mother, the foetus and the infant and in the case of epigenetics to the heritability across generations from grandmother to grandchild. Within the context of social and environmental exposures, the benefits of breastfeeding and infant nutrition, the relationships between early experiences and cognitive development and the development of the executive function which help to control impulsive behaviour have all been commented on extensively.…”
Section: The Evidence Of Mechanismsmentioning
confidence: 99%
“…Previous reviews have made suggestions on improving epidemiological design and translational potential of clinical -omics investigations [2,25]. However, several ongoing studies still adopt cross-sectional designs, although they have inherent methodological challenges in establishing biomarker-disease associations [26], as previously detailed.…”
Section: Case-control Studiesmentioning
confidence: 99%